Development of Scientific Literacy and Pedagogical Content Knowledge (PCK) of Prospective Science Teachers through Lesson Study-Based Courses - A Wahab Jufri; Agus Ramdani; Jamaluddin Jamaluddin; Afriana Azizah (Jurnal Penelitian Pendidikan IPA, 2019)
Lesson Study has been adopted as an effort to improve the quality of education in many countries. Scientific literacy and pedagogical content knowledge (PCK) are two indicators of quality education which most agree are important considerations for science teachers This research has been undertaken by following a lesson study-based action research intervention. The objectives were to analyze its effects on development of prospective science teacher (PST) scientific literacy and PCK indicators. Research subjects were 32 fourth semester PSTs enrolled in Strategies for Teaching Biology course. The research was conducted in three cycles with a plan-do-see phase in each cycle. The data were obtained from PSTs’ tasks and analyzed by comparing the mean score gained for two indicators of scientific literacy and three indicators of students’ PCK. Results of this study indicates that the mean scores gained in each indicator of scientific literacy and PCK were higher in the third and second cycles of lesson study when compared to the first cycle. Therefore it can be concluded that implementing lesson study based action research brought about improvement the PSTs’ scientific literacy and PCK, as well as the quality of teaching and learning processes. Key words: lesson study, scientific literacy, pedagogical content knowledge